On the Boundedness of Solutions of Discontinuous Differential Equations - Santos, Iguer (Trends in Computational and Applied Mathematics, 2021)
By using the notion of Carathéodory solution to differential equations, the present work studies the boundedness of solutions of discontinuous differential equations. For these discontinuous systems determined by discontinuous differential equations, results are obtained that guarantee sufficient conditions to boundedness of solutions in terms of nonsmooth Lyapunov functions.